Current Status and Applications of Genome‐Scale Metabolic Models of Oleaginous Microorganisms - Zijian Hu; Jinyi Qian; Yuzhou Wang; Chao Ye (Food Bioengineering)
ABSTRACT Oleaginous microorganisms have the unique ability to accumulate lipids that can exceed 20% of their dry cell weight under certain conditions. Despite their potential for efficient lipid production, the metabolic pathways involved are not yet fully understood, largely due to the complexity of intracellular processes and the challenges in phenotypic prediction. This review synthesizes the latest research on the application of Genome‐scale Metabolic Network Models (GSMMs) to study oleaginous microorganisms, including bacteria, cyanobacteria, yeast, microalgae, and fungi, and provides a comprehensive analysis of how GSMMs have been utilized to decipher the metabolic mechanisms behind lipid accumulation and to identify key genes involved in lipid synthesis. The review highlights the role of GSMMs in predicting cellular behavior, optimizing metabolic engineering strategies, and discusses the future directions and potential of GSMMs in enhancing lipid production in microorganisms. This comprehensive overview not only summarizes the current state of research but also identifies gaps and opportunities for further investigation in the field.